Aerosol assisted chemical vapour deposition of transparent conductive ZnO thin films with hexagonal microplate surfaces and ultrahigh haze values. Issue 44 (8th October 2015) - Chen, Shuqun; McLachlan, Martyn; Sapelkin, Andrei; Binions, Russell
Abstract : Aerosol assisted chemical vapour deposition has been used to fabricate transparent conductive ZnO thin films with highly hexagonal, textured surfaces and ultra high haze on silica glass substrates. Abstract : We report a novel and facile aerosol assisted chemical vapour deposition (AACVD) approach to fabricate transparent conductive ZnO thin films with highly hexagonal-plate-textured surfaces on silica glass substrates by using zinc-acetate-dihydrate, acetic-acid, deionized water and methanol as a precursor solution.